Self-reflection (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. In both your personal and professional life, reflecting on your thoughts and actions is a valuable tool for improvement. Reflective practice can assist you in better understanding your personal motives, habits, and patterns of behavior. You can use this self-knowledge to make more informed job decisions and collaborate better with others. Today, you'll learn the steps to self-reflection. We'll discuss how to break down and focus on specific areas one at a time. We'll then cover how to use self-reflection to position yourself to achieve your aims through establishing short-term and long-term goals. Learning Objectives Learn how reflective practice can assist you in better understanding your personal motives, habits, and patterns of behavior Learn to use this self-knowledge to make more informed job decisions and collaborate better with others.